Synthesis and Spectral Studies for new Schiff base and its Binuclear Complexes with ZnII,CdII and HgII - Numan, A.T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new ligand (H4L) and its complexes with ( ZnII, CdII and HgII) were prepared. This ligand was prepared in two steps. In the first step a solution of terephthaldehyde in methanol was reacted under reflux with 1,2-phenylenediamine to give an precursor compound which reacted in the second step with 2,4-dihydroxybenzaldehyde to give the ligand. The complexes were then synthesized by direct reaction of the corresponding metal chloride with the ligand. The ligand and complexes were characterized by spectroscopic methods FT-IR, UV-Vis, 1HNMR, and atomic absorption, chloride content, HPLC, mole-ratio determination. in addition to conductivity measurement. The data of these measurements suggest a distorted tetrahedral geometry for ZnII, CdII and HgII complexes and that they would be presented as [M2L(H2L)CI2]. The Stability Constant K and Gibbs free energy âˆ†G were calculated for [Zn2(H2L)Cl2] and [Cd2(H2L)Cl2] complexes by using spectrophotometer method. The obtained values indicate that these complexes are stable in their solution. The biological activity for the following ligand ( H4L ) and complexes [Zn2(H2L)Cl2] and [Cd2(H2L)Cl2] was studied .